Does Medicaid Coverage Increase Access to Health Care after Release from Prison for Adults with a History of Substance Use?. (15th September 2021) - Burns, Marguerite; Cook, Steven; Brown, Lars; Hernandez, Karla; Tyska, Steve; Westergaard, Ryan
Abstract : Research Objective: Substance use disorders (SUDs) are endemic and undertreated among the 1.2 million individuals incarcerated in state prisons. Reentry to the community is characterized by elevated rates of morbidity and mortality, particularly due to drug overdose. Treatment of SUDs before and during the reentry period reduces the risk of relapse and overdose. However, most formerly incarcerated adults with SUD do not receive any treatment in the initial weeks and months post‐release. We estimate the impact of Medicaid enrollment on the likelihood of receiving any health care, and SUD‐related care specifically, in the 30‐days post‐incarceration for adults with a history of substance use. Study Design: We study a natural experiment in which the Wisconsin Department of Corrections introduced prerelease Medicaid enrollment assistance. All adults with income below 100% of the federal poverty level were eligible for Medicaid throughout the study period. Using person‐level longitudinal data that links Corrections and Medicaid data, we implemented two‐stage least squares (2SLS) instrumental variables (IV) analysis. Two variables comprised the instruments corresponding to two policy periods: a 3‐month enrollment assistance implementation period and the fully operational enrollment assistance program. The key assumption is that timing of release is unrelated to the outcomes, conditional on the other variables in the model. Outcomes included care received within 30‐days of release: any outpatient visit (all‐cause, SUD, and opioid use disorder [OUD]), medication for OUD (MOUD), emergency department and inpatient events (all‐cause and drug overdose). Population Studied: The population includes 18, 187 adults ages 18–64 incarcerated by the state, with a history of substance use, who were released between April 2014 – December 2016. Principal Findings: The instruments were correlated with Medicaid enrollment in the month of release (F‐statistic of 455). The likelihood of Medicaid coverage in the month of release increased from 39% at baseline, to 56% after introduction of the enrollment assistance program to 69% after it was fully operational. At baseline, the percentage of adults with health care use within 30‐days of release was 16% for any outpatient visit, 2.5% for an SUD‐related visit, 0.7% for an OUD‐related visit, 0.3% for MOUD, 5.5% for any ED visit, and 0.8% for an inpatient visit. Acquiring Medicaid coverage increased the likelihood of outpatient health care use within 30‐days of release (p < 0.05) by 26 percentage points (pp) for any outpatient visit, 2.6 pp for OUD‐related outpatient visit, 3.6 pp for an SUD‐related outpatient visit, and 1.5 pp for MOUD. Medicaid coverage was not associated with a change in emergency or inpatient care. Conclusions: Medicaid coverage among adults releasing from prison increased immediate access to outpatient care overall and for SUDs specifically for adults with a history of substance use. However, it did not reduce the likelihood of emergency or inpatient care. These findings highlight the important contribution, and potential limitations, of Medicaid coverage alone as a strategy to improve post‐release access to care and reduce overdose risk. Implications for Policy or Practice: Study findings highlight the potential positive impact of the proposed federal Medicaid Reentry Act on access to outpatient care for formerly incarcerated adults during the high‐risk, immediate post‐release period. Primary Funding Source: Wisconsin Partnership Program.